Your CEO succession playbook how to pass the torch so everyone wins - Michael, Natalie (Vancouver. Trifold Publishing, 2017)
For Boards and transitioning CEOs, consider this book your strategic companion from the start of the process right through to the hand-off, and discover how to address common concerns along the way. Learn why a CEO should start a conversation about succession planning early, even if they have no intention of leaving their role anytime soon. Stay above the fray by mitigating and managing power plays. And understand how to build a practical framework to help the departing CEO start a new life chapter that moves from success to significance.
Keywords: CEO